2005
DOI: 10.1080/00016470510030625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on the osteoinductivity of morphogenetic protein extract from reindeer bone

Abstract: Background Bone morphogenetic proteins (BMPs), which are capable of stimulating the production of new bone, must be sterilized before preclinical and clinical use to reduce the risk of infections and associated complications. In this study, we investigated the effects of gamma sterilization on the osteoinductivity of native reindeer BMP extract in the Balb/C mouse thigh muscle pouch model.Methods 5 mg of native reindeer BMP extract and 5 mg of bovine serum albumin were administered separately either in gelatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Until now, there have been no studies investigating the ability of reindeer BMP extract to heal long bone defects. We have shown previously that reindeer BMP extract is an effective inducer of new bone formation in a muscle pouch model in mice (Pekkarinen et al 2003(Pekkarinen et al , 2004(Pekkarinen et al , 2005b. In the present study, we compared the bone healing properties of the reindeer BMP extract to results with untreated and collagen controls, while rhBMP-2 (InductOS) was also included in the comparisons because the bone healing capacity of rhBMP-2 has been well documented in experimental animal and clinical studies (Hollinger et al 1998, Sciadini and Johnson 2000, Yudell and Block 2000, Govender et al 2002, Li et al 2002.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, there have been no studies investigating the ability of reindeer BMP extract to heal long bone defects. We have shown previously that reindeer BMP extract is an effective inducer of new bone formation in a muscle pouch model in mice (Pekkarinen et al 2003(Pekkarinen et al , 2004(Pekkarinen et al , 2005b. In the present study, we compared the bone healing properties of the reindeer BMP extract to results with untreated and collagen controls, while rhBMP-2 (InductOS) was also included in the comparisons because the bone healing capacity of rhBMP-2 has been well documented in experimental animal and clinical studies (Hollinger et al 1998, Sciadini and Johnson 2000, Yudell and Block 2000, Govender et al 2002, Li et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The doses were chosen according to our previous studies (Pekkarinen et al 2003(Pekkarinen et al , 2004(Pekkarinen et al , 2005b(Pekkarinen et al , 2005c. Finally, implants were lyophilized in test tubes for 48 h.…”
Section: Reconstitution Of Implants and Sterilizationmentioning
confidence: 99%
“…In some studies, irradiation has been found to inhibit (Buring and Urist 1967) or only partially destroy (Munting et al 1988, Schwarz et al 1988, Ijiri et al 1994, Zhang et al 1997) the osteoinductive capacity. In others, no effect of irradiation on the osteoinductive capacity has been found (Wientroub and Reddi 1988, Andriano et al 2000, Ripamonti et al 2000, Pekkarinen et al 2005.…”
Section: Histomorphometrymentioning
confidence: 99%
“…These proteins may be released during the resorptive phase of bone graft incorporation, and can have a profound effect on bone cell physiology. Although studies have been performed to determine the effect of irradiation on BMPs (Munting et al 1988, Wientroub and Reddi 1988, Dziedzic-Goclawska et al 1991, Ijiri et al 1994, Andriano et al 2000, Ripamonti et al 2000, Pekkarinen et al 2005, the effect of irradiation on the incorporation process of morselized bone chips remains unclear. We studied the effects of steri-lization by gamma irradiation on the incorporation of impacted morselized allografts.…”
mentioning
confidence: 99%
“…Radiation exposure induces latent TGF-β activation (25,26). Other studies reported that the osteoinductive potential of bone morphogenetic proteins of various origins was preserved after sterilization at 25 kGy (27,28). Growth factors react differently to gamma irradiation: gamma sterilization alters the properties of insulin-like growth factor-1 (29), whereas the TGF-β superfamily is resistant to high doses of radiation.…”
Section: Discussionmentioning
confidence: 99%